Innovative E-Module Design Using the FIVES Model: Strengthening Literacy and Numeracy in Elementary Schools - Sri Dewi Nirmala; Ryan Dwi Puspita (AL-ISHLAH: Jurnal Pendidikan, 2025)
Literacy and numeracy are critical foundations for developing elementary students’ problem-solving and critical thinking skills. To support these competencies, structured e-learning modules are essential. This study explores the design of e-learning modules based on the FIVES learning model—a pedagogical framework consisting of Focus, Inquiry, Vocabulary, Evidence, and Summary—to enhance literacy and numeracy at the elementary level. Using a qualitative, exploratory approach, data were collected through in-depth interviews with eight teachers and classroom observations of eight fourth-grade classes across elementary schools in West Java, DKI Jakarta, Banten, and Lampung. Data were analyzed using the Miles and Huberman model, involving data reduction, display, and conclusion drawing. The findings indicate that effective FIVES-based e-learning modules should include interactive text activities, inquiry-driven tasks, vocabulary development components, and evidence-based comprehension exercises. Customized formative assessments were also identified as essential tools to evaluate students’ literacy and numeracy progress. The modules showed strong potential to support active learning and knowledge construction aligned with students’ developmental needs. The integration of the FIVES model into e-learning design can significantly enhance foundational literacy and numeracy skills through a structured and student-centered approach. Future research should investigate the scalability of these modules, assess their performance in varied educational settings, and explore integration with other digital tools to improve learning outcomes.